2014
DOI: 10.1139/cgj-2013-0194
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the environmental impact of shredded tires as embankment fill material

Abstract: This article deals with the assessment of the environmental impact of shredded scrap tires mixed with sand to build embankments. Pollution of water as well as consequences of fire ignition were considered. Percolation, lixiviation, and lysimeter tests were performed on the raw material as well as on residue resulting from the fire. The collected liquids were analysed considering 200 physicochemical parameters. Their toxicity on a small shellfish and a bacterium was assessed. Measurements were compared with exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 18 publications
1
22
0
2
Order By: Relevance
“…The experimental facet of this study emphasized instrumentation monitoring, to investigate the structure's response and validate the derived numerical models. In addition to the re-use of end-of-life tyres, pollution to the environment and fire risk issues were also addressed (Hennebert et al, 2014). This paper presents the real-scale impact experiments conducted in this study and addresses the impact response of the embankment under different impact energies.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental facet of this study emphasized instrumentation monitoring, to investigate the structure's response and validate the derived numerical models. In addition to the re-use of end-of-life tyres, pollution to the environment and fire risk issues were also addressed (Hennebert et al, 2014). This paper presents the real-scale impact experiments conducted in this study and addresses the impact response of the embankment under different impact energies.…”
Section: Introductionmentioning
confidence: 99%
“…Composition of tires includes 21% of carbon black and 0-15% of silica and particles are emitted by tire wear and found in road runoff water and sedimented in road storm basin [23]. Shredded tires mixed with crushed limestone (to be used as fill material in embankment) did not release particles during a one year-lysimeter study [24]. A second group are ENPs of the synthetic organic pigments (referred in the colour index C.I.…”
Section: French Production and Importation Amounts Of Engineered Nanomentioning
confidence: 99%
“…Hennebert et al (2014) reported that tire rubber only had limited consequences on the environment, and the water quality in the eluates considering a wide range of parameters did not exceed the limits for road applications. Arroyo et al (2011) reported that the self-combustion potential was negligible as long as the amount of corrodible steel in the tire rubber is tightly controlled.…”
Section: Scrap Tires and Their Reuse In Construction Projectsmentioning
confidence: 99%